PEMBERIAN NUTRISI AB MIX PADA LIMBAH AIR KOLAM DENGAN MENGGUNAKAN SISTEM HIDROPONIK BERPOTENSI MENINGKATKAN PERTUMBUHAN TANAMAN SAWI (Brassica juncea L) - Amirul Mukminin; Agus Sutanto; Muhfahroyin muhfahroyin (BIOLOVA, 2020)
Abstract: Sometimes fish poop often causes problems because of its unpleasant odor and makes the pound dirty, but it has some advantages. The rest of the foods made sediment in the bottom of the pound, also have some advantages. Both of these wastes that come from the result of pound cultivation could be used for hydroponic. The waste of catfish pound compound nitrogen and phosphor that come from the feces, the rest of the food, and the urine of the fist that have high protein. Nitrogen and phosphor are very important for the growth of the plant. To know is the waste of the fish pound could be useful for the growth of the plant, it needed to do some experiment about the effect of fish pound waste toward the growth of the plant. This experiment aims to know the effect of fish pound waste toward the growth of the plant. This experiment grouping treatment into two groups. The first group is the group with the treatment of given the AB nutrition mix to the catfish and carp pound. The second group is the group with the treatment of given the wastewater of catfish and carp pound.